Raising the Stakes: Cassava Seed Networks at Multiple Scales in Cambodia and Vietnam - Delaquis, Erik; Andersen, Kelsey F.; Minato, Nami; Cu, Thuy Thi Le; Karssenberg, Maria Eleanor; Sok, Sophearith; Wyckhuys, Kris A. G.; Newby, Jonathan C.; Burra, Dharani Dhar; Srean, Pao; Phirun, Iv; Le, Niem Duc; et al. (Frontiers in Sustainable Food Systems, 2018)
Cassava is one of the most important annual crops in Southeast Asia, and faces increasing seed borne pest and disease pressures. Despite this, cassava seed systems have received scant research attention. In a first analysis of Vietnamese and Cambodian cassava seed systems, we characterized existing cassava seed systems in 2016–2017 through a farmer survey based approach at both national and community scales, with particular focus on identifying seed system actors, planting material management, exchange mechanisms, geographies, and variety use, and performed a network analysis of detected seed movement at the provincial level. Despite their status as self-organized “informal” networks, the cassava seed systems used by farmers in Vietnam and Cambodia are complex, connected over multiple scales, and include links between geographically distant sites. Cassava planting material was exchanged through farmer seed systems, in which re-use of farm-saved supply and community-level exchanges dominated. At the national level, use of self-saved seed occurred in 47 and 64% of seed use cases in Cambodia and Vietnam, respectively. Movement within communes was prevalent, with 82 and 78% of seed provided to others being exchanged between family and acquaintances within the commune in Cambodia and Vietnam, respectively. Yet, meaningful proportions of seed flows, mediated mostly by traders, also formed inter-provincial and international exchange networks, with 20% of Cambodia's seed acquisitions imported from abroad, especially neighboring Vietnam and Thailand. Dedicated seed traders and local cassava collection points played important roles in the planting material distribution network at particular sites. Sales of planting material were important means of both acquiring and providing seed in both countries, and commercial sale was more prevalent in high-intensity than in low-intensity production sites. Considerable variability existed in local seed networks, depending on the intensity of production and integration with trader networks. Adapted innovations are needed to upgrade cassava seed systems in the face of emerging pests and diseases, taking into account and building on the strengths of the existing systems; including their social nature and ability to quickly and efficiently distribute planting materials at the regional level.